The War That Won’t Go Away - Moore, Bob (BMGN - Low Countries Historical Review, 2013)
This review contrasts the sometimes moralising Dutch historiography on the Second World War with the more detached approaches taken by Anglophone scholars on the same subjects, and suggests that many of the charges made against Chris van der Heijden’s work (Dat nooit meer. De nasleep van de Tweede Wereldoorlog in Nederland [Never Again: The Aftermath of the Second World War in The Netherlands]) from within the Netherlands would not have seemed so important in this wider constituency. At the same time, it takes issue with some elements of his writing style and the importance he ascribes to specific trends and features of Dutch postwar memory. This review is part of the discussion forum ’Dat nooit meer’ (Chris van der Heijden).